Implementasi Metode Weighted Product Dalam Pengambilan keputusan Penilaian Kinerja Karyawan - Misrawati Aprilyana Puspa; Marlin Lasena; Hariati Husain; Zainudin Sidik (Bulletin of Information Technology (BIT), 2023)
Employees are people involved in the company organization to carry out their duties based on their position or position. The current employee performance appraisal process is still carried out manually so that the element of subjectivity is very high, in addition to the relatively large number of employees making the employee determination time longer and sometimes late. The purpose of this study is to design a Decision Support System for employee performance appraisal at Otanaha Hospital so that the appraisal process and the decisions obtained are appropriate. The method used is the Weighted Product Method because this method is more efficient and the time needed in calculations is shorter and easier. The system is designed with php and html programming. Database used MySql language, with modeling using Unified Modeling Language. The result of this study is that it can make it easier for Otanaha hospital to assess and view employee data information and the results of performance appraisals of honorary employees and civil servants